1996
DOI: 10.1002/j.1551-8833.1996.tb06541.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic removal by ferric chloride

Abstract: Source water composition affects removal efficiency. Bench‐scale studies were conducted in model freshwater systems to investigate how various parameters affected arsenic removal during coagulation with ferric chloride and arsenic adsorption onto preformed hydrous ferric oxide. Parameters included arsenic oxidation state and initial concentration, coagulant dosage or adsorbent concentration, pH, and the presence of co‐occurring inorganic solutes. Comparison of coagulation and adsorption experiments and of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
206
0
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(216 citation statements)
references
References 23 publications
3
206
0
7
Order By: Relevance
“…As(III) is more mobile in groundwater and 25-60 times more toxic than As(V). The concentration of arsenic species is mainly dependent on redox potentials (Masscheleyn et al, 1991) and pH (Hering et al, 1996). Under low pH and mildly reducing conditions (>100 mV), As(III) is thermodynamically stable and exists as arsenious acid (H 3 AsO 0 3 , H 2 AsO À 3 , HAsO 2À 3 and AsO 3À 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As(III) is more mobile in groundwater and 25-60 times more toxic than As(V). The concentration of arsenic species is mainly dependent on redox potentials (Masscheleyn et al, 1991) and pH (Hering et al, 1996). Under low pH and mildly reducing conditions (>100 mV), As(III) is thermodynamically stable and exists as arsenious acid (H 3 AsO 0 3 , H 2 AsO À 3 , HAsO 2À 3 and AsO 3À 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used technologies include coagulation and precipitation with iron and aluminum salts (Edwards, 1994;Hering et al, 1996), adsorption onto activated alumina, activated carbon and activated bauxite (Gupta and Chen, 1978), ion exchange and reverse osmosis (Clifford, 1999). Some recent treatment technologies based on oxidation and adsorption are green sand filtration (Christen, 2000), iron oxide coated sand (Joshi and Chaudhuri, 1996), manganese dioxide coated sand (Bajpai and Chaudhuri, 1999), ferruginous manganese ore (Chakravarty et al, 2002), ferrihydrite (Jain et al, 1999), clay minerals (Manning and Goldberg, 1997) and zero-valent iron (Fendorf et al, 1997;Farrell et al, 2001;Su and Puls, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies by other researchers have indicated that precipitation of Fe-As and Mn-As phases is very unlikely. The introduction of ferric ions for removal of arsenic from hydrometallurgical processed solutions and in water treatment has been studied by many researchers (Robins et al, 1987;Edwards, 1994;Cheng et al, 1994;Hering et al, 1996). These studies indicated that coagulation and adsorption are the major mechanisms for arsenic removal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ferric ion has been used as an effective coagulation reagent in the treatment of arseniccontaminated wastewater (Cheng et al, 1994;Edwards, 1994;Hering et al, 1996). A study by Krause and Ettel (1988) showed that arsenic can form relatively insoluble ferric iron compounds, which have solubility products on the order of 10−20 to 10−24.…”
Section: In Situ Chemical Fixation Batch Experimentsmentioning
confidence: 99%